Implementation of Sharia-Based AI to Enhance SME Performance - Maulana; Usman Jafar; Murtiadi Awaluddin; Sumarlin (www.amertainstitute.com, 2024)
This study explores the application of Artificial Intelligence (AI) based on Islamic principles within the small and medium-sized enterprises (SMEs) sector in Indonesia. With a focus on ethical aspects aligned with Sharia values, the research identifies AI's potential to enhance operational efficiency, consumer trust, and business reputation for SMEs operating in predominantly Muslim markets. Using a qualitative literature review approach, the study analyzes previous findings related to Sharia-compliant AI applications, highlighting benefits such as increased consumer loyalty through principles of fairness, transparency, and integrity. The results reveal that Sharia-based AI can contribute to sustainable business practices, providing a competitive advantage in markets sensitive to ethical considerations. Additionally, the research emphasizes that Sharia-compliant AI design is more accessible to SMEs with limited resources, supporting smoother adoption and increased operational sustainability. Recommendations include developing supportive policies for ethical AI integration, fostering affordable AI solutions, and further encouraging empirical research to evaluate the long-term financial and social impacts of Sharia-based AI on SMEs. This study contributes to the growing body of knowledge on ethical AI in business and provides practical guidance for policymakers, technology developers, and SMEs seeking to integrate Sharia-compliant AI for enhanced competitiveness and consumer loyalty.